Project Management Methods in Projects Co-financed by EU Funds - Košťálová, Jana; Tetřevová, Liběna; Paták, Michal (My University, 2017)
This paper deals with the management of projects co-financed by European Union funds (structural funds and the Cohesion Fund) in the Czech Republic (EU projects). The authors aimed to analyze and assess the scope of familiarity with basic project management methods and their application within the implementation of EU projects in the Czech Republic in the Programming Period 2007-2013. Based on a questionnaire survey of EU project organisers, the authors evaluate their attitudes to project management methods as effectiveness improvement tools. The analysis also considers the degree of dependence between familiarity with project management methods, their application, and their effectiveness as perceived by EU project organisers. Finally, it presents recommendations to the institutional authorities and project organisers with respect to applications during the Programming Period 2014-2020. We can state that project management methods were not applied to a sufficient extent. To improve the effectiveness of the implementation of EU projects, EU fund provider's methodical instructions have to include the obligations or recommendations to apply project management methods, mainly methods applicable within more project management knowledge areas and within more project life cycle stages (i.e. Logical Framework, Pre-Project Study with Formalized Structure, Formalized Risk Analysis and Formalized Project Communication Plan).
Metody projektového řízení v projektech spolufinancovaných z EU fondů
Keywords: Project; Project Management; Project Management Methods; European Union Funds; Projects Co-Financed by the European Union Funds; projekt; projektové řízení; metody projektového řízení; fondy Evropské unie; projekty spolufinancované z fondů Evropské unie